2011
DOI: 10.1128/jvi.01120-10
|View full text |Cite
|
Sign up to set email alerts
|

Natural Suppression of Human Immunodeficiency Virus Type 1 Replication Is Mediated by Transitional Memory CD8+T Cells

Abstract: HIV replication is suppressed in vitro by a CD8 + cell noncytotoxic antiviral response (CNAR). This activity directly correlates with an asymptomatic clinical state. The objective of this study was to identify the phenotype of CD8 + cell subsets having strong CNAR activity. CD8 + cell subset frequencies and CNAR levels were measured for human immunodeficiency virus (HIV)-uninfected individuals and three groups of HI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(48 citation statements)
references
References 55 publications
(70 reference statements)
2
45
0
1
Order By: Relevance
“…It should be noted that we used a conservative sorting scheme that did not account for all CD8 ϩ T cells, and recent studies have suggested that CD8 ϩ T cells with HIV-1-inhibitory activity may have phenotypes different from those described here (18,28). Functional studies of virus-specific CD8 ϩ T cells have shown that the markers used in this study also do not perfectly distinguish between central and effector memory CD8 ϩ T cells, and there is some plasticity in the expression of surface markers depending on the activation state (15,26,39,52,(54)(55)(56).…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that we used a conservative sorting scheme that did not account for all CD8 ϩ T cells, and recent studies have suggested that CD8 ϩ T cells with HIV-1-inhibitory activity may have phenotypes different from those described here (18,28). Functional studies of virus-specific CD8 ϩ T cells have shown that the markers used in this study also do not perfectly distinguish between central and effector memory CD8 ϩ T cells, and there is some plasticity in the expression of surface markers depending on the activation state (15,26,39,52,(54)(55)(56).…”
Section: Discussionmentioning
confidence: 99%
“…Cell surface expression of CD107a is associated with the capacity of antigen-specific CD8 ϩ T cells to eliminate infected cells and to inhibit HIV-1 replication. Phenotypic markers denoting transitional memory cells are also associated with the ability to inhibit HIV-1 replication (18,30). Furthermore, the characterization of the cytokine profile of CD8 ϩ T cells has identified MIP-1␤ as a correlate of virus control (16) and virus inhibition (18).…”
Section: Identification Of the Functional Properties Of Cd8mentioning
confidence: 99%
“…Because CNAR appears during early primary infection and suppresses all HIV-1 and HIV-2 isolates via secretion of CAF, it has features of an innate immune response [44,45]. Healthy asymptomatic individuals, particularly LTSs, exhibit increased frequencies of the CD8 1 cells that mediate CNAR in comparison to those who progress to AIDS [46,47]. Moreover, studies of SIV-infected rhesus monkeys depleted of CD8 1 cells in vivo suggest that the virus level is maintained by a CD8 1 cell noncytotoxic process [48,49].…”
Section: Regulatory T (T Reg ) Cellsmentioning
confidence: 99%
“…Another finding is that HIV-specific CTLs are often functionally immature [64] or exhausted and are therefore unable to respond appropriately to their cognate antigens [65]. However, these cells may exhibit CNAR [47]. Observations of HIV-specific CTL responses in HIV-exposed uninfected individuals [66] have given some credibility to the concept of a vaccine that elicits protective CTL activity.…”
mentioning
confidence: 99%